2008
DOI: 10.1007/s00449-008-0205-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic synthesis of the chiral side-chain of statins: application of an alcohol dehydrogenase catalysed ketone reduction on a large scale

Abstract: The chemoenzymatic synthesis of the tert-butyl (S)-6-chloro-5-hydroxy-3-ketohexanoate is described. Our approach relies on a highly regio- and enantioselective reduction of a beta,delta-diketohexanoate ester catalysed by NADP(H)-dependent alcohol dehydrogenase of Lactobacillus brevis (LBADH). A detailed description of the scale-up of the enzymatic synthesis of the hydroxyketo ester is given which includes a scale-up of the substrate synthesis as well, i.e. the preparation of diketo ester on a 100 g scale. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Many biphasic systems have been developed for LBADH: TONs higher than 10 4 were found for the biphasic system water-tert-buthyl methyl ether (MTBE) with LBADH after optimization. 16 The partition coefficient between the two phases of the substrates and products is an important issue. Indeed it was demonstrated that an ionic liquid, [BMIM][(CF 3 SO 2 ) 2 N], is more favourable to the conversion than MTBE.…”
Section: Reaction In Dense Propanementioning
confidence: 99%
See 1 more Smart Citation
“…Many biphasic systems have been developed for LBADH: TONs higher than 10 4 were found for the biphasic system water-tert-buthyl methyl ether (MTBE) with LBADH after optimization. 16 The partition coefficient between the two phases of the substrates and products is an important issue. Indeed it was demonstrated that an ionic liquid, [BMIM][(CF 3 SO 2 ) 2 N], is more favourable to the conversion than MTBE.…”
Section: Reaction In Dense Propanementioning
confidence: 99%
“…Processes with ADHs in non-aqueous solvents are rare due to their instability in these media, 14 consequently, biphasic systems are often chosen instead of a non-aqueous media when water immiscible products are involved. Processes with LBADH were run in several biphasic systems with organic solvents 15,16 and patented several times.…”
Section: Introductionmentioning
confidence: 99%
“…oxohexanoate ((S)-CHOH) is a highly valuable chiral building block, because it can be further converted to chiral building block 1 for the synthesis of atorvastatin, as well as the key hydroxyl-substituted chiral intermediate 2, which is used for the synthesis of rosuvastatin (Scheme 1). The enzymatic asymmetric reduction of tert-butyl 6-chloro-3,5-dioxohexanoate (CDOH), which can be effectively synthesized from the corresponding Meldrum's acid intermediate (Jackson et al 2012), represents a promising strategy for the synthesis of (S)-CHOH (Wolberg et al 2001(Wolberg et al , 2008 (Scheme 1). To date, a few of alcohol dehydrogenases (ADHs) have been reported to exhibit highly regioselectivity and enantioselectivity toward the reduction of CDOH, some with (R)-selectivity (Wolberg et al 2004), only two with the desired (S)-selectivity to produce (S)-CHOH (Wolberg et al 2001;Weckbecker and Hummel 2006).…”
Section: Introductionmentioning
confidence: 99%
“…ADH from L. brevis is a versatile enzyme, which catalyzes the reduction of carbonyl compounds stereoselectively by oxidising the cofactor NADPH. It is currently used for the synthesis of methyl (R)-3-hydroxybutanoate, tert-butyl (S)-6-chloro-5-hydroxy-3-ketohexanoate and fluorinated hydrins (Wolberg et al 2001(Wolberg et al , 2008Borzęcka et al 2013). It has a broad substrate spectrum which includes aromatic ketones and keto-esters and is the reason for the growing interest in the ADH of L. brevis as a catalyst for other redox reactions (Leuchs and Greiner 2011).…”
Section: Introductionmentioning
confidence: 99%